X‐ray exposure in cryoballoon versus radiofrequency ablation for atrial fibrillation over 7 years: A single center study. Issue 6 (23rd September 2022) - Heinroth, Konstantin; Blum, Tilman; Drexler, Max; Plehn, Alexander; Hartkopf, Thomas; Horenburg, Charlotte; Sedding, Daniel
Abstract: Background: Facing an increasing number of radiofrequency ablation (RF) and cryoballoon ablation (CB) procedures for treatment of AF radiation exposure and its reduction is a focus point for interventional electrophysiologists. Objective: This study evaluated the procedural parameters of the different ablation methods focusing on radiation exposure and the BMI of the patients. Methods: One thousand one hundred and thirty‐three first procedural cases of pulmonary vein isolation in patients with paroxysmal and persistent AF treated with RF and CB‐based techniques were analyzed retrospectively over a period of 7 years focusing on the endpoints dose area product (DAP, cGycm 2 ), fluoroscopy time (FT, min) and procedural time (PT, min). Results: Of the 1133 patients (mean age 63.4 ± 11.4 years, BMI 28.9 ± 4.7) 335 patients received an RF procedure, 211 patients were treated with the cryoballoon first generation (CB1), and 587 patients with cryoballoon second generation (CB2), respectively. The mean DAP for the PVI was 508 ± 654 cGycm 2 in RF procedures, 1077 ± 683 cGycm 2 in CB1‐procedures, and 587 ± 489 cGycm 2 in CB2‐procedures with fluoroscopy times significantly shorter in RF procedures (9.6 ± 5.2 min) as compared to 17.7 ± 5.9 min in CB1‐ and 16.3 ± 6.3 min in CB2‐procedures ( p  < .001). At the same time, the procedure duration using RF (115 ± 33.5 min) was significantly longer than both in CB1 (96 ± 16.8 min) and CB2 procedures (75 ± 15.9 min). Conclusions: Despite longer fluoroscopy durations in the CB technique, the CB2 resulted in a comparable low radiation exposure in PVI as compared to RF, accompanied by shorter procedure durations. Abstract : 1133 first procedural cases of pulmonary vein isolation in patients with paroxysmal and persistent AF treated with RF and CB based techniques were analyzed retrospectively over a period of 7 years focusing on the endpoints dose area product (DAP, cGycm²), fluoroscopy time (FT, min) and procedural time (PT, min). Despite longer fluoroscopy durations in the CB‐technique, the CB2 resulted in a comparable low radiation exposure in PVI as compared to RF, accompanied by shorter procedure durations.